2011 IEEE Vehicular Networking Conference (VNC) 2011
DOI: 10.1109/vnc.2011.6117118
|View full text |Cite
|
Sign up to set email alerts
|

Approximating safe spacing policies for adaptive cruise control strategies

Abstract: Abstract-In the development of Cooperative Adaptive Cruise Control (CACC) systems, spacing policies are primarily developed for optimisation of string stability and traffic stability. However, the safety issue is hardly taken into account. Uncertainty in the communication network and sensor information makes deciding upon a safe minimal headway a non-trivial task. In this paper, we propose a model that is able to approximate the minimal safe time headway, given uncertainty of parameters with varying velocities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Their simulation results show that small disturbances are damped through the platoon. And in [63], the uncertainties in the communication network and sensor information were studied. The uncertainty parameters and delays were approximated to be Gaussian distributed, and this model was used to calculate the minimal time headway for safety.…”
Section: Vehicle Longitude Dynamicsmentioning
confidence: 99%
“…Their simulation results show that small disturbances are damped through the platoon. And in [63], the uncertainties in the communication network and sensor information were studied. The uncertainty parameters and delays were approximated to be Gaussian distributed, and this model was used to calculate the minimal time headway for safety.…”
Section: Vehicle Longitude Dynamicsmentioning
confidence: 99%
“…Shladover et al (2010) identified that drivers maintain 2.2 s, 1.6 s, and 1.1 s time gaps for 31.1%, 18.5%, and 50.4% of their vehicle-following time in ACC mode, respectively, and drivers maintain 0.6 s, 0.7 s, 0.9 s, and 1.1 s time gaps for 57%, 24%, 7%, and 12% of their vehicle-following time in CACC mode, respectively [24]. Willigen et al (2011) recommended a distance headway and a time headway for each platoon size (i.e., 20 and 30) and operating mode (i.e., ACC, CACC with transmitted accelerations, and CACC with estimated accelerations) (see Table 8) [25]. Horiguchi and Oguchi (2014) calculated distance gap for vehicles in CACC mode based on minimum safe distance gap, follower's speed, leader's speed, maximum acceleration, and maximum deceleration [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that the system was capable of damping small disturbances throughout the platoon. The uncertainties in communication network and sensor information were modeled by a Gaussian distribution in [18], which was applied to calculate the minimal time headway for safety reasons. Qin et al [19] studied the effects of stochastic delays on the dynamics of connected vehicles by analyzing the mean dynamics.…”
Section: Introductionmentioning
confidence: 99%